2022
DOI: 10.3389/fcell.2022.851613
|View full text |Cite|
|
Sign up to set email alerts
|

Potential of Cellular Therapy for ALS: Current Strategies and Future Prospects

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive upper and lower motor neuron (MN) degeneration with unclear pathology. The worldwide prevalence of ALS is approximately 4.42 per 100,000 populations, and death occurs within 3–5 years after diagnosis. However, no effective therapeutic modality for ALS is currently available. In recent years, cellular therapy has shown considerable therapeutic potential because it exerts immunomodulatory effects and protects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 228 publications
(236 reference statements)
0
9
0
Order By: Relevance
“…Preclinical findings support this, and ongoing phase I and II clinical trials in ALS patients indicate positive results in safety and tolerability. However, substantial improvements for ALS patients necessitate continued collaboration between basic and clinical researchers [ 67 , 68 ].…”
Section: Motor Neuron Disordersmentioning
confidence: 99%
“…Preclinical findings support this, and ongoing phase I and II clinical trials in ALS patients indicate positive results in safety and tolerability. However, substantial improvements for ALS patients necessitate continued collaboration between basic and clinical researchers [ 67 , 68 ].…”
Section: Motor Neuron Disordersmentioning
confidence: 99%
“…They found that serum C4 levels in ALS patients were lower than in the healthy control group [ 33 ]. Depending on the understanding of the role of the immune system in motor neuron diseases and the developments in drug technology, some studies investigating the effectiveness of immune modulator biological agents in the treatment of motor neuron disease have started [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that results in the progressive loss of motor neurons in the brain and spinal cord [43]. An increased aggregation of superoxide dismutase 1 (SOD1), decreased phosphorylation of cyclic adenosine mono phosphate-response element-binding protein (CREB) and reduced activation of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) lead to the development of mitochondrial dysfunction, which is frequently observed in patients suffering from ALS [43]. Accordingly, restoration of mitochondrial function is an important therapeutic goal in the treatment of ALS [43].…”
Section: Beneficial Effects Of At-msc-exos In the Treatment Of Neuroi...mentioning
confidence: 99%
“…An increased aggregation of superoxide dismutase 1 (SOD1), decreased phosphorylation of cyclic adenosine mono phosphate-response element-binding protein (CREB) and reduced activation of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) lead to the development of mitochondrial dysfunction, which is frequently observed in patients suffering from ALS [43]. Accordingly, restoration of mitochondrial function is an important therapeutic goal in the treatment of ALS [43]. Lee and colleagues showed that AT-MSC-Exos attenuated aggregation of SOD1, induced phosphorylation of CREB, and activated PGC-1α, which resulted in the restoration of mitochondrial function [44].…”
Section: Beneficial Effects Of At-msc-exos In the Treatment Of Neuroi...mentioning
confidence: 99%